Sampling for cassava production survey, Brazil - Jones, Peter G. (International Center for Tropical Agriculture, 1986)
THE METHOD USED TO SAMPLE THE MUNICIPALITIES FROM CASSAVA GROWING REGIONS IN ORDER TO CARRY OUT A CASSAVA PRODUCTION SURVEY IN BRAZIL IS DESCRIBED. IN STAGE 1, A MAP OF LATIN AMERICAN CASSAVA PRODUCTION WAS USED TO SELECT MAJOR ZONES OF INTEREST IN THE STATES OF PARA, MARANHAO, PERNAMBUCO, BAHIA, AND RIO GRANDE DO SUL. IN STAGE 2, THE LIMITS OF THE CHOSEN AREAS WERE TRANSFERRED TO A LARGER SCALE AND SUBDIVIDED INTO REGIONS BASED ON AN INTERPRETATION OF CLIMATE AND SOIL DATA; 84 AGROECOZONES WERE IDENTIFIED AND WITHIN THESE, 1525 MUNICIPALITIES. IN STAGE 3, A FINAL LIST OF 320 CANDIDATE MUNICIPALITIES RESULTED IN 25 MARKED AGROECOZONES. A RANDOM SELECTION OF 50 MUNICIPALITIES WAS MADE. EACH ONE OF THE SELECTED AGROECOZONES IS BRIEFLY DESCRIBED. (CIAT)